Evaluation of the Impact of Central Bank of Nigeria’s (CBN) Monetary Policy and its Instruments on the Economy - EKWEOZOR, Celestine Izunna (Research Parks Publishers, 2023)
This work evaluated the impact of the Central Bank of Nigeria monetary policy and its instruments on the economy for a period of 22 years spanning 2000 to 2022. With data drawn from CBN’s statistical bulletins, gross domestic product (GDP) proxied for economic growth (dependent variable), and the monetary policy variables (independent variables) are monetary policy rate (MPR), loan to deposit ratio (LTDR), liquidity ratio (LR) and cash reserve ratio (CRR). During the period under review, loan-to-deposit-ratio appeared the most monetary policy variables used to influence economic activities in Nigeria. The unit root analysis for stationarity results using the Augmented Dickey Fuller revealed that the variables were stationary or integrated at level 1(0) and first differencing 1(1), which informed the use of the ARDL technique of estimations. Results emanating from the estimation revealed the existence of long run relationship between monetary policy initiatives and economic performance in Nigeria. The error correction mechanism (ECM) term showed a 66.13% speed of convergence to equilibrium. Thence, it recommends monetary and fiscal policies unionism since each compliments the other, adoption of a forward-looking approach, data-driven decision, movement in government expenditure like financing of deficit budgets and monetization of deficits.